Coaching without a compass: Why the Philippines needs a national framework for coaching education - Balore, Julibert Jr Noynoyan; Suniga, John Paul C.; Jurek, Joanna Michalina (Universitas Tanjungpura, 2025)
Background and Study Aim. Coaches play a critical role in athlete development, yet coaching education in the Philippines remains fragmented, decentralized, and under-regulated. Despite the growing success of Filipino athletes on the international stage, the absence of a national framework has resulted in inconsistent certification standards, limited access to continuing professional development (CPD), and uneven opportunities for career progression. This study aims to address this gap by proposing a unified National Coaching Education Framework (NCEF) for the Philippines. Material and Methods. The study employed a policy-oriented approach that combined a structured literature review with comparative policy analysis of international models such as Canada